Trade in health services - Chanda Rupa (The World Health Organization, 2002)
In light of the increasing globalization of the health sector, this article examines ways in which health services can be traded, using the mode-wise characterization of trade defined in the General Agreement on Trade in Services. The trade modes include cross- border delivery of health services via physical and electronic means, and cross-border movement of consumers, professionals, and capital. An examination of the positive and negative implications of trade in health services for equity, efficiency, quality, and access to health care indicates that health services trade has brought mixed benefits and that there is a clear role for policy measures to mitigate the adverse consequences and facilitate the gains. Some policy measures and priority areas for action are outlined, including steps to address the "brain drain"; increasing investment in the health sector and prioritizing this investment better; and promoting linkages between private and public health care services to ensure equity. Data collection, measures, and studies on health services trade all need to be improved, to assess better the magnitude and potential implications of this trade. In this context, the potential costs and benefits of trade in health services are shaped by the underlying structural conditions and existing regulatory, policy, and infrastructure in the health sector. Thus, appropriate policies and safeguard measures are required to take advantage of globalization in health services.